Niobium oxides and niobates physical properties: Review and prospects. (July 2016) - Nico, C.; Monteiro, T.; Graça, M.P.F.
Abstract : Abstract: For the last 75 years several studies have been reporting on the physical properties of niobium oxides, but there is still many contradictory, inconsistent and insufficient information on these metal oxides. This review will begin by describing the niobium oxygen system and the different stoichiometric and non-stoichiometric phases, specifically Nb, NbO, NbO2, Nb2 O5 and Nb2 O5−δ . The crystalline phases and polymorphs of these materials are often inconsistently identified in different works and thus, a clarification of the nomenclature of the several niobium oxides polymorph and their crystalline structure is also presented. Due to their interesting physical properties, many applications of these materials have been suggested such as solid electrolytic capacitors, catalysis, photochromic devices, transparent conductive oxides or memristors, becoming obvious that a good understanding of niobium oxides physical properties and their control is essential and urgent. Additionally, a short review on different types of niobates, namely alkali niobates, columbite niobates and rare earth niobates and the relation of the properties of these materials with niobium oxides will be presented.